Evaluation of memory performance in patients with brain disorders following rTMS treatment. A systematic review. (March 2022) - Bonotis, Konstantinos; Anargyros, Konstantinos; Liaskopoulos, Nikolaos; Barlogianni, Anna-Maria
Highlights: There is converging evidence for memory improvement in patients with brain disorders following rTMS treatment. A remarkable percentage of positive results was found in patients with mild cognitive impairment and Alzheimer's disease. Future research should consider properly designed treatment protocols including longitudinal follow-up. Abstract: Objective: Repetitive transcranial magnetic stimulation (rTMS) is being used as a non-invasive, non-pharmacological treatment with emerging clinical applications. The objective of this systematic review is to assess the possible rTMS effect on memory performance in patients suffering from central nervous system diseases. Methods: PubMed, Google Scholar, Science Direct and Cochrane Library were searched through April 2021 for rTMS clinical trials in neuropsychiatric conditions, assessing pre-post treatment patients' memory performance with neuropsychological measures. Results: One hundred and four clinical studies were included for evaluation. Overall, a large number of reports were detected with a positive outcome of patients' memory performance, concerning primarily the working memory, whereas there were also inconsistent results. In particular, considerable results were observed in patients with mild cognitive impairment and early stage Alzheimer's disease. Conclusions: Despite the variability of reports and the limited ability to generalize our findings, this review offers further evidence regarding the possible use of rTMS as a memory enhancement tool. Significance: The study provides an updated and broad review in the field and highlights the need for more adequate studies, focusing on treatment procedure characteristics, follow-up and maintenance options of this approach.